Kajian gelagat selamat pelajar di dalam makmal kejuruteraan kimia di universiti awam Malaysia - Khairul Hafezad, Abdullah (2021)
Accidents in university laboratories are a global issue. Therefore, university laboratory safety management must emphasise safety ethics and safe laboratory behaviour to promote a more comprehensive laboratory safety culture. This study aims to investigate the direct effect of safety leadership on laboratory safety behaviour among university students based on the S-O(BAMP)-R model. Besides, safety knowledge, safety commitment, and safety motivation are also examined as mediating effects. Meanwhile, personality trait is scrutinised as a moderating effect. The study is based on a survey engaging 361 students studying chemical or chemistry-based engineering programs at five public universities in Malaysia. The data were analysed using IBM SPSS Statistics and SEM SmartPLS 3.3.2. The findings disclosed that safety leadership could construe a positive significant direct effect on the laboratories’ safety behaviour. Therefore, the management of the universities should emphasise the essence of high-quality safety leadership among the lecturers. This study also demonstrated that safety knowledge and safety commitment could mediate safety leadership and safety behaviour in the laboratory. Conversely, the mediating effect of safety motivation and the personality traits’ moderating effect failed to designate a significant impact. In this study, the mediating result of safety commitment is the most contributing factor relative to safety behaviour, and attention should be paid to maintaining laboratory safety at the universities. Besides, studies on the influence of safety leadership and safety behaviour in the laboratory should also be explored in other educational organisations such as private higher education institutions (IPTS), teacher education institutes (IPG), and community colleges. This study, finally, discusses the theoretical and practical implications of the S-O(BA)-R model derived from the original S-O(BAMP)-R model and future research suggestions.